Exploratory study on determinants of problem loan among non-bank financial institution in Malaysia - M. T., Hirnissa; Mohd Ashhari, Zariyawati; R., Fadilla (Academia Industry Networks, 2020)
Problem loan (PL) deteriorates the NBFI performance as it can cause the firm to encounter financial distress. NBFI management and managers need to manage the lending activities properly to mitigate the problem loan from occurring by determining the factors that influence the PL. Hence, this study is conducted to investigate the determinants of problem loan Malaysian NBFI for the period of 10 years which is from the year 2008 to the year 2017. The result Panel Data analysis shows that deposit growth and firm credit growth positively associated with problem loans. NBFI management of managers should consider deposit growth and firm credit growth while performing lending in creating income. This may be avoiding the bank to encounter financial distress and performance deterioration.